Financial system in the economic transition period: The case of the Lao PDR - Chanthavong, Somvixay (Journal of Management, Economics, and Industrial Organization, 2021)
Financial system plays a key role in allocating the investment fund from household savings to the corporate sector, and increases the risk sharing among individuals and the firms. The understanding of timely financial market participation is hence crucial, particularly in the country that is on the journey of graduation from the least developed country, called Lao People’s Democratic Republic. This research therefore focuses on prescribing the transition of financial system by providing the story of financial development evolution from first independent period and present direction. This pioneer article aims to create the clear understanding on how the Lao financial institutions have been formed up periodically, and what the principal strategies are presented from government in responding to the economic change of the nation. As the result, we find that the financial system in Laos seems to have impressive growth during the transition period, while the foreign branches have mostly covered and been large size in term of total assets comparing to other bank categories. This identifies a significant challenge for local banks in regard to the competition condition. Hence, we recommend considering more proper strategies on foreign own banks aiming to utilize their asset to financial intermediation as well as prevent them from having too large market power.